The oldest ever brush hut plant remains from Ohalo II, Jordan Valley, Israel (19,000 BP) - Nadel, Dani
Introduction \Architectural remains of dwellings are extremely rare in Upper Palaeolithic (c. 45,000-20,000 BP) and early Epipalaeolithic (c. 20,000-12,500 BP) sites in the Near East (e.g. Bar-Yosef & Belfer-Cohen 1989; 1992; Henry 1989; Garrard et al. 1994; Goring-Morris 1995; Marks 1976; 1977). Typical for these sites are scattered remains of tools and waste made of flint, animal bones and -- in some sites -- isolated hearths. In rare cases human burials were also discovered. Although there are many tens of sites, hut remains are extremely rare. The only examples are the partially preserved hut floors from Jilat 6 Phase A (c. 16,000 BP, Garrard et al. 1994) and Ein Gev I (c. 15,000 BP, Arensburg & Bar-Yosef 1973; Bar-Yosef 1978). At Ohalo II, a submerged site radiometrically dated to 19,400 years BP, excellent preservation conditions created a unique situation where a variety of organic remains were protected from the elements. The remains of three brush